168k views
0 votes
You are given f(0) = 1 and g(0) = -2 and g(1) = 3. What is
g ∘ f ( 0 )
equal to?

User Thorstenvv
by
4.5k points

1 Answer

6 votes

Answer:

  • g∘f (0) = 1

Step-by-step explanation:

The composition of the functions f and g represented by g ∘ f ( 0 ) means that g is applied to f(0), i.e f(0) is the input to the function g.

Since f(0) = 1, you are going fo find g(1):


\( g\circ f(x)=g(f(x)) \)\\\\\( g\circ f(0)=g(f(0)) \)\\\\\( g\circ f(0)=g(1) \)=3

User Andrey Petrov
by
5.0k points